2020
DOI: 10.1021/acs.est.0c00383
|View full text |Cite
|
Sign up to set email alerts
|

Lake Huron’s Phosphorus Contributions to the St. Clair–Detroit River Great Lakes Connecting Channel

Abstract: The United States and Canada called for a 40% load reduction of total phosphorus from 2008 levels entering the western and central basins of Lake Erie to achieve a 6000 MTA target and help reduce its central basin hypoxia. The Detroit River is a significant source of total phosphorus to Lake Erie; it in turn has been reported to receive up to 58% of its load from Lake Huron when accounting for resuspended sediment loads previously unmonitored at the lake outlet. Key open questions are where does this additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…For example, Scavia et al 8 suggested that if the Lake Huron P load cannot be decreased, and further reduction from the system's major water treatment plant (WTP) is not considered because it has already met its target, then other watershed sources will need to decline by 72% to meet an overall 40% reduction target�a significant challenge that needs additional evaluation. Scavia et al 18 subsequently used a hydrodynamic model, satellite images of resuspension events and ice cover, wave hindcasts, and continuous turbidity measurements at the outlet of Lake Huron to provide evidence that this additional P load, in the form of sediment transport, is from wave-induced resuspended Lake Huron sediment, primarily within 30 km of the Ontario nearshore. They also suggested that the additional load increased over time as ice cover decreased due to climate warming.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, Scavia et al 8 suggested that if the Lake Huron P load cannot be decreased, and further reduction from the system's major water treatment plant (WTP) is not considered because it has already met its target, then other watershed sources will need to decline by 72% to meet an overall 40% reduction target�a significant challenge that needs additional evaluation. Scavia et al 18 subsequently used a hydrodynamic model, satellite images of resuspension events and ice cover, wave hindcasts, and continuous turbidity measurements at the outlet of Lake Huron to provide evidence that this additional P load, in the form of sediment transport, is from wave-induced resuspended Lake Huron sediment, primarily within 30 km of the Ontario nearshore. They also suggested that the additional load increased over time as ice cover decreased due to climate warming.…”
Section: ■ Introductionmentioning
confidence: 99%